"Lung sparing growth": is the lung not affected by malnutrition?. Issue 4 (6th April 2017) - Korten, Insa; Usemann, Jakob; Latzin, Philipp
Malnutrition is a major cause of mortality and morbidity in developing countries [1]. It has been reported to play a role in different acute and chronic disease conditions [2–4], including respiratory diseases and lung development [5, 6]. Starting in utero, maternal malnutrition during pregnancy may influence postnatal lung function directly ( e.g. through decreased alveolar number), or indirectly ( e.g. through intrauterine growth retardation, prematurity or low birth weight) [7]. There is clear evidence of detrimental effects of vitamin A deficiency in pregnancy on lung function in childhood [8]. Early postnatal malnutrition was associated with several adverse pulmonary effects and lung injury in animal models, e.g. decreased lung protein and DNA synthesis in the lungs [9], whereas breastfeeding and balanced nutrition is thought to be protective [10, 11]. Furthermore, Vitamin D and C deficiency have been reported to cause deficits in lung function and structure [12, 13]. To summarise, malnutrition potentially influences respiratory health and lung function on multiple levels. "Lung sparing growth": intriguing hypothesis to explain why the lung is not affected by severe acute malnutrition http://ow.ly/9V5d309M1ho